1991
DOI: 10.1212/wnl.41.3.409
|View full text |Cite
|
Sign up to set email alerts
|

Plasma exchange in chronic progressive multiple sclerosis

Abstract: Plasma exchange (PE) was shown in a previous double-blind randomized controlled study to confer significant additional benefit at 1 year upon patients with chronic progressive multiple sclerosis (CPMS) treated with immunosuppressive drug therapy (ISDT). Efficacy over an extended term, indications for retreatment, and long-term toxicity are dealt with in this analysis of a larger number of patients. During the past 7 years, 200 patients with CPMS have been treated with PE and low-dose ISDT at this center. Impro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
17
0

Year Published

1995
1995
2009
2009

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 0 publications
0
17
0
Order By: Relevance
“…Some studies suggested a benefit [3][4][5][6], but they were often confounded by concurrent immunosuppressant usage. Others did not demonstrate a benefit [7][8][9][10] including two randomised, blinded, sham controlled studies [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies suggested a benefit [3][4][5][6], but they were often confounded by concurrent immunosuppressant usage. Others did not demonstrate a benefit [7][8][9][10] including two randomised, blinded, sham controlled studies [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Based on our experience of over 30 years and 30,000 PLEX procedures on hundreds of MS patients, as well as two double-blind, randomized, controlled studies [2,3], we can say that the response to PLEX in the two aforementioned cases is not atypical. We have learned that the most important prognostic factor for recovery with PLEX is the severity of disease progression in the previous 2 years [4]. Thus, the higher the rate of progression, the greater the response to PLEX.…”
mentioning
confidence: 99%
“…Thus, the higher the rate of progression, the greater the response to PLEX. Based on multiple clinical characteristics of responders and nonresponders in our studies, we have published a table whereby if you know the age, duration of the disease, and severity of progression in the previous 2 years, you can predict with significant accuracy the degree of improvement you can expect with PLEX [4].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Ellison not only praised the ÔÔadequacyÕÕ of this trial, but considered it a ÔÔtarget for others to match or exceedÕÕ [3]. A subsequent longterm follow-up study [4] of PE in 200 progressive MS patients was also ignored by the author. This study [4] established the beneficial long-term effects of PE, as well as offered a table that can predict the clinical outcome following PE.…”
mentioning
confidence: 99%